Research of electric car dynamics - Lyutenko, Vasyl; Nesterenko, Mykola; Durachenko, Hryhoriy; Nesterenko, Mykola (Academic journal Industrial Machine Building Civil Engineering, 2019)
Recently, electric vehicles are becoming widespread throughout the world, so the research is relevant. The results of performedresearches of dynamics electric car on the basis of ZAZ-1102 are presented. The calculation method of dynamic loadsin electric and mechanical systems of electric cars is developed. The technique considers the electromagnetic processes in theengine, the elasticity of the elastic parts, the oscillatory processes, and damping in the elastic links. On the basis of the developedmathematical model and using the mathematical software apparatus MathCAD, calculations of transients in the electricand mechanical systems have been obtained, based on the obtained results of the research, the constructed graphs.The obtained results of the study of the electric motor drive mechanism can be used for designing, calculating and determiningthe dynamic loads of electric cars and their hybrids.
Keywords: mathematical model; electric car; drive; mechanical and electrical systems; dynamic loads; flexibility; electromechanical processes; oscillatory phenomena